Title: Developmental validation of Y-SNP pedigree tagging system: A panel via quick ARMS PCR. (May 2020) - Yin, Caiyong; Ren, Yijie; Adnan, Atif; Tian, Junzhe; Guo, Kejian; Xia, Mingying; He, Ziwei; Zhai, Dian; Chen, Xueyun; Wang, Lei; Li, Xin; Qin, Xingjun; et al.
Highlights: To resolve the complicated relationships within Y-STR haplotypes, special importance was given to Y chromosomal SNPs. Based on CE technology, a novel Y-SNP Pedigree Tagging System typed via rapid ARMS-PCR was proposed. Typing profiles were consistent within male relative pairs and showed the different distribution patterns of male groups. The introduction of Y-SNPs into forensic practices may enhance the male pedigree discriminability hopefully. Abstract: The Y chromosomal short tandem repeats (Y-STRs) have been used widely to establish paternal relatedness and examine sub-structures in different geographical regions. However, the applications of Y-STRs showed their limitations when it comes to resolving the complicated relationships within close relatives or among unrelated individuals from different geographic areas. Here, we overcome these limitations by introducing a new strategy for Y-SNP multiplex typing using rapid ARMS (amplification-refractory mutation system) PCR. Newly developed Y-SNP Pedigree Tagging System is able to profile 24 Y-SNPs in a single reaction while the whole process takes 4−5 hours. The panel precisely defines the 11 haplogroups (E-M96, D-JST021355, N-M231, C-M130, O-P186, I-M170, IJ-M429, K-M9, QR-M45, G-M201, and IJK-M522) and 13 sub-haplogroups (D1a1a1-N1, D1a2a-P47, C2-M217, N1a1-M46, O1a-M119, O1b-M268, O1b2-M176, O2-M122, O2a1-KL1, O2a2-P201, O2a2b-P164, O2a2a1a2-M7 and O2a2b1a1-M117). This system could contribute to providing the haplogroup affiliation of unknown pedigree and resolving the sub-structures of East Asian populations. In this study, the multiplex system was validated for: ability to detect degraded DNA, sensitivity, species specificity, reproducibility/repeatability, stability, performance in different scenarios, mixture studies, PCR amplification conditions, and population surveys. The Y-SNP information showed a consistent pattern within 40 father-son or brother-brother pairs. The results of this multiplex system showed the different distribution patterns of male donors from two Chinese Han populations. In this study, we try to discriminate the suspect's pedigree on the level of Y-SNP haplogroups. These results show that Y-SNP Pedigree Tagging System is a robust and reliable amplification kit which can be used for male haplogroup determination.